Evaluation of the Antimicrobial Activity of Ethanol Extract from Galangal Rhizome (Kaempferia galanga L.) in the Purbalingga Accession - Subaryanti, Subaryanti; Musrifah, Siti; Bahri, Saiful (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2025)
Galangal (Kaempferia galanga L.) is a medicinal plant known for its antimicrobial properties. Its rhizome contains bioactive compounds such as alkaloids, flavonoids, tannins, phenols, quinones, steroids, and triterpenoids, which have been reported to inhibit the growth of Staphylococcus epidermidis, Propionibacterium acnes, and Candida albicans. This study aimed to evaluate the antimicrobial activity of the ethanol extract of galangal rhizome from the Purbalingga accession. The antimicrobial activity was assessed using the disc diffusion method to determine the inhibition zone diameter (IZD), while the minimum inhibitory concentration (MIC) and minimum killing concentration (MKC) were determined using solid agar dilution. Extract concentrations of 10%, 30%, 50%, 70%, and 90% were tested for IZD. Clindamycin was used as a positive control for S. epidermidis and P. acnes, while nystatin was used for C. albicans; 10% DMSO served as the negative control. MIC values were evaluated at concentrations of 1.25%, 2.5%, 5%, and 10%. The ethanol extract inhibited the growth of S. epidermidis at a concentration of 10%, with an IZD of 8.38 mm. The inhibition zones for P. acnes and C. albicans were 8.42 mm and 9.24 mm, respectively. The MIC was 10% for S. epidermidis and 2.5% for both P. acnes and C. albicans. The MKC for P. acnes and C. albicans was determined to be 5%. The ethanol extract of K. galanga rhizome from the Purbalingga accession exhibits antimicrobial potential against S. epidermidis, P. acnes, and C. albicans, suggesting its potential use in antimicrobial applications